PENERAPAN METODE RESITASI UNTUK MENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU BAHAN SISWA KELAS X TPD SMK MUHAMMADIYAH PRAMBANAN - Heri Kiswanso; Suparmin Suparmin (Jurnal Taman Vokasi, 2016)
The aims of this research are: (1) to know what the application of methodics resitasi learning approaches can enhance the student’s activeness especially on the material knowledge; and (2) to know what the methodics resitasi approaches can enhance the academic result of student especially on the material knowledge. The hypothesis of this research is a methodics resitasi which can increase students  activeness and results of the study on student material knowledge at X grade SMK Muhammadiyah Prambanan.The type of this research was an action research (PTK). The subjects in this study are students of X grade TPD of 31 students.  The data collection technique used observation sheets, test techniques, and documentation. Test instrument was implemented in class of X TPD SMK Muhammadiyah Prambanan. Data analysis techniques used by a percentage to the activeness of the study and quantitative analysis techniques which include the average absorbance values.The result of the analysis can be described as follows: (1) the methodics resitasi can increase the activeness of the learners on learning subjects of material knowledge X grade SMK Muhammadiyah Prambanan, Sleman. The  average activeness of the students was on the cycle I of 62,09%  rise to 82,72%  on cycle II ; and (2) learning activity used resitasi methodics can improve the students on material knowledge subjects of  X grade SMK Muhammadiyah Prambanan, Sleman. It can be seen from the average value of study on pre-test 55,16 rise on post-test cycle I became 79,67 on cycle II becomes 88,38, whereas if viewed from the pre-absorbance test increased by 16,12% following the action on the cycle I of 70,96%, rise in cycle II becomes 83,87%.